RETROSPECTIVE ANALYSIS OF RESEARCH ON BUSINESS PROCESS MANAGEMENT THEORY IN THE BUILDING SECTOR OF THE ECONOMY - Glukh, Vadym (Public Management and Policy, 2025)
The article examines the diversity and scope of approaches used by scientists around the world and in Ukraine to study the content, necessity, and prospects for further development of the concept of business process management in general, and in the construction industry in particular. The relevance of the study is determined by the expediency of using approaches to business process management in order to increase the competitiveness of construction companies, as well as an effective way for modern business transformation. Successful implementation and active application of elements of the business process management mechanism are possible provided that there is a comprehensive understanding of its conceptual provisions and directions of development. The objectives of the study were to determine the place and role of business process management in the social sciences from the perspective of historical development, to reveal the content of its evolutionary and key principles of modernization, and to justify its acceptability for use in the manufacturing sectors of the domestic economy. The research methodology involved conducting a bibliometric analysis of scientific publications in two leading scientometric databases, Scopus and Web of Science. These databases reflect academic achievements and provide a comprehensive overview of research from 1997 to the present. The results of the bibliometric analysis are crucial for determining priorities in research and developing effective business process management strategies in the current conditions of sustainable development of companies in the construction industry. The results of the analysis confirm the obvious trend in the scientific direction of business process management towards the active use of information technologies. Thus, the very concept of business process management is becoming interdisciplinary in nature, going beyond the boundaries of pure management in terms of its content and practical implementation mechanisms. The research also revealed a clear trend towards specialization and localization of business process management, taking into account regional and industry-specific characteristics. The most cited scientific works are those that reveal the content of the methodology and practical achievements of integrating digital tools with the principles of corporate culture to facilitate the implementation of business process management mechanisms in the relevant areas of business structures. In this context, the authors of the publications actively explore the relationship between business process management and the digital (information) integration of economic sectors.